Penuras kuasa aktif pirau satu fasa menggunakan strategi kawalan ringkas - Yusof, Y.; Umar, R.Z.R.; Rahim, N.A. (Penerbit UTM Press, 2017)
This paper describes a single phase shunt active power filter system used in compensating current harmonics and improving electrical line’s power factor via simplified control strategy based on estimation of nonlinear load’s equivalent resistance. By employing MATLAB Simulink simulation tool, the proposed control strategy successfully compensated source current harmonics and corrected line power factor to near unity. Moreover, analysis on the system performance indicated that the system’s achieved fast time response, stabilized system and near zero steady state error. To verify the proposed system, experimental results also presented.